(untitled) (Itinera, 2018)
This paper addresses Walter Benjamin’s commentary on the poems of the cycle “Handbook for City-Dwellers” by Bertolt Brecht, in order to discuss the specificity of Brechtian lyricism in the realm of Benjamin’s reflexions on modern urban lyric. Benjamin resumes two decisive issues to the constitution of Brecht’s work: the sobriety of language and teaching as a form of transmission of urban and political experience. This link between experience and transmission is not reduced to the instruction of survival conditions in the city. It is constituted by the learning of a critical attitude related to the city. While communication between isolated individuals is precarious and the political organization illegal, the poems seek to build a bond between “I” and “you” by the poetic reflection on the urban experience.